Social capital and utilization of immunization service: A multilevel analysis in rural Uttar Pradesh, India - Md Zabir Hasan; Lorraine T. Dean; Caitlin E. Kennedy; Akshay Ahuja; Krishna D. Rao; Shivam Gupta (Elsevier, 2020)
The National Health Policy (2017) of India advocates Universal Health Coverage through inclusive growth, decentralization, and rebuilding a cohesive community through a participatory process. To achieve this goal, understanding social organization, and community relationships - defined as social capital - is critical. This study aimed to explore the influence of individual and community-level social capital on a critical health system performance indicator, three-doses of diphtheria-pertussis-tetanus (DPT3) immunization among 12-59 month children, in rural Uttar Pradesh (UP), India. The analysis is based on a cross-sectional survey from two districts of UP, which included 2239 children 12-59 months of age (level 1) from 1749 households (level 2) nested within 346 communities (level 3). We used multilevel confirmatory factor analysis to generate standardized factor scores of social capital constructs (Organizational Participation, Social Support, Trust and Social Cohesion) of the household heads and mothers both at individual and community level, which were then used in the multilevel logistic regressions to explore the independent and contextual effect of social capital on a child's DPT3 immunization status. The result showed only community-level Social Cohesion of the mothers was associated with a child's DPT3 immunization status (Adjusted odds ratio = 1.25, 95% confidence interval = 1.12-1.54; p = 0.04). Beyond its independent effect on utilization of immunization service, the collective Social Cohesion of the mothers significantly modified the relationship of child age, mother's knowledge of immunization, community wealth, and communities' contact with frontline workers with immunization status of the child. With a strong theoretical underpinning, the result substantially contributes to understanding the individual and contextual predictors of immunization service utilization and further advancing the literature of social capital in India. This study can serve as a starting point to catalyze social capital within the health interventions for achieving wellbeing and the collective development of society.